ASSESSMENT OF THE RISK OF SCAR STRICTURE OF THE ANAL CANAL DEPENDING ON THE CHOICE OF TREATMENT METHOD FOR HEMORRHOIDECTOMY (Multidisciplinary Journal of Science and Technology, 2024)
Assessment of the risk of scar stricture of the anal canal depending on the choice of treatment method for hemorrhoidectomy